Association of Muscle Radiodensity and Muscle Mass With Thoracic Aortic Calcification Progression in Dialysis Patients - Xiao‐xu Wang; Jing‐yuan Cao; Yao Wang; Min Li; Shi‐mei Hou; Zhen Zhao; Min Yang; Ping‐ping Ju; Yu‐jia Jiang; Jing‐jie Xiao; Ri‐ring Tang; Hong Liu; et al. (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background Recent findings have spotlighted sarcopenia as a critical factor exacerbating cardiovascular risk in dialysis patients. However, no studies have investigated the relationship of muscle characteristics with thoracic aortic calcification (TAC). We explored whether skeletal muscle radiodensity (SMD) and skeletal muscle index (SMI) are associated with TAC in dialysis patients. Methods In this study, 2517 dialysis patients (between January 2020 and June 2023) from four centres with chest computed tomography (CT) scans were analysed cross‐sectionally. A cohort of 544 initial‐dialysis patients (between January 2014 and December 2020) was followed for TAC progression. Chest CT images were used to assess SMD and SMI at the L1 level, as well as to measure the scores of TAC, including ascending TAC (ATAC), aortic arch calcification (AoAC) and descending TAC (DTAC). Multivariable linear regression models were employed to assess the effects of SMD and SMI on TAC and its progression. Restricted cubic spline was used to assess the potential non‐linear relationships of SMD and SMI with TAC progression. Results The mean (SD) age for the cross‐sectional study was 54.8 (14.0) years, with males accounting for 58.2%. Over a mean (SD) follow‐up duration of 3.45 (1.82) years, 85.7% showed TAC progression. Comparing the highest quartile of SMD to the lowest quartile, a significant inverse association was observed with TAC (β, −1.08 [−1.42 to −0.75]; p < 0.001); similar trends were noted for SMI (β, −0.42 [−0.74 to −0.10]; p = 0.011). SMD and SMI as continuous variables were also both significantly negatively correlated with TAC. In the longitudinal study, multivariable linear regression models revealed that an increase of 1 SD in SMD resulted in a decrease of 0.10 SD (95% CI, −0.17 to −0.02; p = 0.011) in TAC progression, and an increase of 1 SD in SMI resulted in a decrease of 0.12 SD (95% CI, −0.20 to −0.04; p = 0.003) in TAC progression. Restricted cubic spline models excluded non‐linear trends for the relationships of SMD and SMI with TAC progression. The associations of SMD and SMI with DTAC were consistent with those observed for TAC, but neither showed a significant association with ATAC. Conclusions Higher SMD and higher SMI were significantly associated with lower TAC and its progression in dialysis patients. Improving SMD and SMI could be a new approach for reducing TAC.